The Effect Of Mass Ratio On The Flow Characteristics Of Hydrogen-natural Gas Mixture Using Reduced Order Modelling - Norazlina Subani; Norsarahaida Amin (Penerbit UTM Press, 2024)
Non-Indexed Publication